Surgical management of odontogenic cysts involving the maxillary sinus- a retrospective study. Issue 8 (August 2020) - Safadi, Ahmad; Kleinman, Shlomi; Gigi, Dana; Wengier, Anat; Oz, Itay; Abergel, Avraham; Koren, Ilan; Ungar, Omer J.
Abstract: Objective: To describe our strategy for the management of odontogenic cysts involving the maxillary sinus, and to define the role of transnasal endoscopic sinus surgery in the treatment algorithm. Methods: A retrospective study was conducted. Included were all consecutive patients with odontogenic cysts involving the maxillary sinus who were treated in a single medical center between 2011 and 2019. Their medical records were reviewed for demographic data, preoperative presentation, surgical approach, final pathology, and postoperative course. Odontogenic cysts were classified as small or large according to maxillary sinus extension within or beyond the alveolar recess, respectively. Results: A total of 30 patients with odontogenic cysts involving the maxillary sinus were treated by a team of maxillofacial and endoscopic sinus surgeons during the study period. There were 11 cases of dentigerous cysts, 11 radicular cysts, seven odontogenic keratocysts (OKCs), and one glandular cyst. Sixteen cases were managed by transnasal endoscopic sinus surgery alone and 14 were managed by a combined intraoral and endoscopic sinus surgery approach. A total of 22 patients had large cysts and total resection was achieved in 20 of them. There was one case of OKC recurrence during an average follow-up of 31 months. No major complications were recorded. Conclusions: The endoscopic approach can serve as an alternative to the transalveolar or lateral window approach. The endoscopic approach is associated with low morbidity and low recurrence rates.